(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article highlights the relevance of communicative competence in the preparation of translators for their profession. The purpose of the research is that communicative competence includes a person’s ability to effectively communicate with others, as well as his ability to express his thoughts and needs through language and non-language means. The development of competence in research methods, especially the important aspects of translation studies education, were studied. Because in this field, it is necessary not only to know the language, but also to effectively organize intercultural communication, to deliver information in different languages ​​in a clear and understandable manner. The article also analyzes theoretically different points of view of future specialists for the development of communicative competence. The results of the research show that communicative competence is important in the personal and professional development of translators. Communicative competence is presented as a criterion for successful communication and social relations.